WANT TO BECOME A SPLUNK ENGINEER? HERE’S WHAT I WISH I KNEW STARTING OUT - RAHUL BHATIA (IPHO-Journal of Advance Research in Science And Engineering, 2026)
Observability engineering turns diverse machine data into understanding of systems for operations, reliability, and security. Does this mean anything? Platforms like Splunk can ingest, index, correlate, and visualize almost any kind of heterogeneous data, but their scope is so broad they easily overwhelm beginners and create silos. The roadmap in this article is based on years of experience designing and building Splunk applications and consists of the steps necessary to evolve from a casual user to an experienced Splunk engineer. To get there, you must learn how the data pipeline works and gain expertise in SPL, native log formats, and an increasingly complex personal Splunk lab. It also explores the modular architecture, packaging of extensions, and knowledge objects to enable scalable analytics and reusable operational intelligence. It concludes by showing engineers how using structured preparation for certifications and scenario-based interviews can convert their private technical knowledge into evidence of engineering judgment in the workplace.